Differential mRNA accumulation upon early arabidopsis thaliana infection with ORMV and TMV-Cg Is associated with distinct endogenous small RNAs Level - Zavallo, Diego; Debat, Humberto Julio; Conti, Gabriela; Manacorda, Carlos Augusto; Rodriguez, Maria Cecilia; Asurmendi, Sebastian (2017)
Small RNAs (sRNAs) play important roles in plant development and host-pathogen interactions. Several studies have highlighted the relationship between viral infections, endogenous sRNA accumulation and transcriptional changes associated with symptoms. However, few studies have described a global analysis of endogenous sRNAs by comparing related viruses at early stages of infection, especially before viral accumulation reaches systemic tissues. An sRNA high-throughput sequencing of Arabidopsis thaliana leaf samples infected either with Oilseed rape mosaic virus (ORMV) or crucifer-infecting Tobacco mosaic virus (TMV-Cg) with slightly different symptomatology at two early stages of infection (2 and 4dpi) was performed. At early stages, both viral infections strongly alter the patterns of several types of endogenous sRNA species in distal tissues with no virus accumulation suggesting a systemic signaling process foregoing to virus spread. A correlation between sRNAs derived from protein coding genes and the associated mRNA transcripts was also detected, indicating that an unknown recursive mechanism is involved in a regulatory circuit encompassing this sRNA/mRNA equilibrium. This work represents the initial step in uncovering how differential accumulation of endogenous sRNAs contributes to explain the massive alteration of the transcriptome associated with plant-virus interactions